ANALYSIS OF PRODUCTION FACTORS FOR GILLNET FISHING GEAR AT THE TECHNICAL IMPLEMENTATION UNIT (UPT) OF THE FISHERY PORT OF RIAU PROVINCE - Brown, Arthur; Hasanah, Camelia Nurul; Nasution, Polaris (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
Dumai City relies entirely on marine waters for its fisheries production, with gillnets being a predominant fishing gear among local fishermen. Gillnets, characterized by their rectangular shape with varying mesh sizes, utilize floats and weights. This study aimed to identify the factors influencing gillnet catches in Dumai City. Results from simultaneous testing revealed that all production factors significantly impact catch quantities. Through multiple linear regression analysis, it was determined which factors exerted positive and negative effects. The regression equation, Y = 0.108 – 0.183 X1 – 0.411 X2 – 0.345 X3 + 0.173 X4 + 0.116 X5 + 0.451 X6 + 0.181 X7 – 0.106 X8 + 0.223 X9, elucidated these relationships. The cumulative effect of production factors on catches amounted to 64.20%. This study provides valuable insights into optimizing gillnet fishing practices in Dumai City's marine environment.